Sustainable harvesting of Tenualosa Toli in Sarawak / Noriham Bujang - Bujang, Noriham (2014)
This research concerns the sustainable harvesting of the Tenualosa toli (T. toli) fish in Sarawak. T. toli is already on the brink of extinction due to unlimited fishing of the species in all of Sarawak’s rivers. Modem technology has increased fishing capacity year by year. This has resulted in the decline of the landings of T. toli fish. Hence, fishing activities have become less profitable due to over harvesting of T. toli in Sarawak’s rivers. Therefore, it is essential to estimate harvesting at maximum sustainable yield, HMSY in order to ensure that T. toli can be continuously harvested and to protect the fish from becoming extinct. This research will attempt to determine the effort at maximum sustainable yield, EMSY of T. toli using the Schaefer model and the Fox model. These models are surplus production model which are useful when limited data are available. The Schaefer model incorporates the logistic growth model to capture the population dynamics whereas the Fox model incorporates the Gompertz growth model to capture the population dynamics. The intrinsic growth rate, the carrying capacity and the catchability coefficient are estimated from the catch and effort data. These values are needed to estimate HMSY and EMSY. This research will add to the body of knowledge regarding sustainable harvesting policies that will ensure a continuous sufficient supply of T. toli. The appropriate level of fishing effort and the corresponding sustainable biomass growth can be suggested to the regulating body that oversees fishing operations. If this species can be replenished, the abundance of T. toli may spur other related fish products such as fish oil from T. toli which is rich in omega-3 and omega-6.